2020
DOI: 10.1111/nph.16307
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizas for a sustainable world

Abstract: More than 80% of plant species exchange resources with mycorrhizal fungi and these associations impact both partners at multiple scales, from individuals to ecosystems. In total, 172 participants from 33 countries and 160 institutions met at the 10 th International Conference on Mycorrhiza (ICOM 10) in the city of M erida in the Yucatan peninsula in Mexicoan area famous for its Mayan archaeological sites, cenotes, and the Chicxulub impact crater that marks the end of the Cretaceous period. They discussed lates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…The increased AM fungi colonization in plants grown under elevated CO 2 conditions may have been due to an increased plant demand for nutrients and enlarged root biomass caused by greater C assimilation [ 24 ]. However, some studies have reported no response or even a decrease in root AM levels in plants grown under high CO 2 concentrations [ 12 , 28 ]. The extent to which eCO 2 impacts the crop–AM association remains unclear [ 10 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased AM fungi colonization in plants grown under elevated CO 2 conditions may have been due to an increased plant demand for nutrients and enlarged root biomass caused by greater C assimilation [ 24 ]. However, some studies have reported no response or even a decrease in root AM levels in plants grown under high CO 2 concentrations [ 12 , 28 ]. The extent to which eCO 2 impacts the crop–AM association remains unclear [ 10 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biofertilization with fungi is based on the mutualistic and symbiotic associations of fungi with certain plant roots, specifically the so-called mycorrhizae. Over 90% of all plant species make these associations, which offer benefits to the plant as well as the fungi [ 10 , 11 , 12 ]. Fungi may be classified into three groups: endomycorrhiza, ectomycorrhiza, and ectendomycorrhiza.…”
Section: Introductionmentioning
confidence: 99%
“…AMF are a type of obligate biotroph that form mutualistic symbiotic associations with the roots of plants [ 22 ]. AMF are also commonly used as biofertilizers for enhancing growth and crop productivity [ 23 ]. In addition to plant growth, AMF provide tolerance to host plants against several fungal pathogens and help in survival under stressful conditions [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…One challenge of using AM associations for food security is that the effect of AM fungal colonization on plant growth and nutrition is highly variable and dependent on many factors. The list of interacting factors is lengthy (see Pickles, Truong, Watts‐Williams, & Bueno, 2020 for a comprehensive list), but the main drivers include: plant species and variety choice, soil physical characteristics, including nutrient availability and biological characteristics (microbiome), and colonizing AM fungal species, abundance, and diversity. The variation in plant growth response to AM fungal colonization in diverse plant genotypes has been illustrated in many staple food crops such as bread wheat (Zhu, Smith, Barritt, & Smith, 2001), durum wheat (Ellouze et al., 2015), and sorghum (Watts‐Williams et al, 2019).…”
Section: Introductionmentioning
confidence: 99%